Effect of Ligustri Lucidi Fructus on myelosuppression in mice induced by cytoxan. (4th November 2022) - Han, Jiahong; Fei, Xuan; Sun, Nian; Xing, Junjia; Cai, Enbo; Yang, Limin
Abstract: In this study, we aimed to demonstrate the therapeutic effect of Ligustri Lucidi Fructus on chemotherapy‐induced myelosuppression and elucidate its mechanism. A pharmacological study was conducted to investigate the mechanism of the inhibiting effects of Ligustri Lucidi Fructus on cyclophosphamide‐induced bone marrow suppression in mice. HPLC was used to measure the chemical components. We demonstrated that medium and high doses of Ligustri Lucidi Fructus increased the amount of white blood cells and bone marrow nucleated cells ( p  < 0.05) in the cyclophosphamian‐induced mouse model, and at the same time reduced granulocyte–macrophage–colony stimulating factor and thrombopoietin in the serum of myelosuppression mice ( p  < 0.01). Medium and high doses of Ligustri Lucidi Fructus can also adjust the thymus index and spleen index( p  < 0.05). Ligustri Lucidi Fructus regulates the balance of bcl‐2/bax, inhibits the expression of Caspase‐3 and meanwhile stimulates the expression of mitogen‐activated protein (MEK) and phospho extracellular regulated protein kinases (p‐ERK) on the MAPK pathway. Five chemical constituents of Ligustri Lucidi Fructus, which may be related to myelosuppression, were analyzed. The content of specnuezhenide was 0.281%, that of ligustroflavone was 0.004%, that of salidroside was 0.094%, that of hydroxytyrosol was 0.060% and that of tyrosol was 0.069%. The effect of Ligustri Lucidi Fructus on myelosuppression after chemotherapy may be related to its multicomponent and multitarget nature. Ligustri Lucidi Fructus may be a promising potential drug for treatment after chemotherapy.